Assessing fundamental motor skills proficiency in school-based sports physical education programs: implications for talent development - Makaruk, Hubert; Webster, E. Kipling; Porter, Jared; Makaruk, Beata; Bodasińska, Anna; Zieliński, Janusz; Tomaszewski, Paweł; Nogal, Marta; Starzak, Marcin; Śliwa, Marcin; Banaś, Michał; Biegajło, Michał; et al. (Frontiers in Sports and Active Living, 2025)
IntroductionFundamental motor skills (FMS) are essential for fostering physical literacy, supporting talent development, and promoting public health in school-aged populations. This study aimed to evaluate FMS proficiency among students in school-based sports physical education (PE) programs, which offer sport-specific training, and compare it to students in traditional PE programs. A secondary aim was to examine whether these programs promote early specialization or early diversification in youth sport development.MethodsA cross-sectional analysis was conducted on 1,332 students (ages 10–14; 58% boys) from 12 schools across Poland, including 547 students in school-based sports PE programs and 785 in traditional PE. The Fundamental Motor Skills in Sport (FUS) test, a qualitative and process-oriented assessment tool, was used to evaluate FMS across six motor tasks: hurdles, jumping rope, forward roll, ball bouncing, ball throwing and catching, and kicking and stopping a ball. Participants were further categorized by sport: boys into basketball, track and field, soccer, and volleyball; girls into basketball, track and field, and volleyball.ResultsOverall, FMS proficiency was at an “insufficient” level in both groups, with 72% of boys and 77% of girls in school-based sports PE programs, and 90% of boys and 92% of girls in traditional PE programs. Additionally, the analysis revealed a predominant emphasis on early specialization within school-based sports PE programs.ConclusionsBoth school-based sports and traditional PE programs fail to ensure adequate FMS proficiency in students. The sport PE programs' curricular focus on early specialization over diversification may further restrict opportunities for motor competence development, with potential consequences for lifelong physical activity and the early stages of talent development.